Mecanismo de alocação de recurso fuzzy para sistemas de gerenciamento de workflow - Jeske, Joslaine Cristina (2016)
In this paper, an approach based on a fuzzy hybrid Petri net model is proposed to solve the resource allocation problem of Workflow Management Systems. Initially, an ordinary Petri net model is used to show the main activities of the system and the diferent routings of the Workflow Process. Hybrid resource allocation mechanisms are modeled by hybrid Petri net with discrete transitions where discrete resources represent equipment and continuous resources represent employees availability. To express in a more realistic way the resource allocation mechanisms when human behavior is considered, fuzzy sets delimited by possibility distributions of the triangular form are associated with the marking of the places which represent human availability. New firing rules and the fuzzy marking evolution of the new model are defined. Such a fuzzy resource allocation model is applied to an example of resource allocation mechanism of a Handle Complaint Process". Finally, a token player algorithm is applied to the model in order to obtain an acceptable scenario corresponding to a specific sequence of activities which respects the time constraints.